Insegnare moduli di “Arte, Scienze e Tecnologie di Rappresentazione Grafica”: quali sfide per il futuro? - Agata Lo Tauro (GEOmedia, 2014)
The battle between neo-idealists and scientists at the turn of the XX century that resulted in stereotypes about the role of science in Italian education has survived mo re or less unchanged and unchallenged to these days. This app roach has created a situation in which a traditional method on research and experimentation is now required based on the different needs of each student, as well as those of tod ay's markets. Professors therefore need to develop skills to enable students to visualise and interpret “reality” (e.g. Natural and Cultural Heritage) in order to co ntribute to other disciplines, in particular within the co ntext of an Open Knowledge and Content and Language Integrated Learning (CLIL ) “novel app roaches”. This exercise isn’t simp ly design based, but requires several aproaches such as the reclassification of schoo ls and educational institutions not simp ly as voc ational and technical edpucational establishments, but mo tivational too , thus mo re closely respo nding to soc ietal needs.